2018
DOI: 10.1103/physrevb.98.220505
|View full text |Cite
|
Sign up to set email alerts
|

Novel pairing mechanism for superconductivity at a vanishing level of doping driven by critical ferroelectric modes

Abstract: Superconductivity (SC) occurring at low densities of mobile electrons is still a mystery since the standard theories do not apply in this regime. We address this problem by using a microscopic model for ferroelectric (FE) modes, which mediate an effective attraction between electrons. When the dispersion of modes, around zero momentum, is steep, forward scattering is the main pairing process and the self-consistent equation for the gap function can be solved analytically. The solutions exhibit unique features:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 45 publications
(53 reference statements)
1
36
1
Order By: Relevance
“…repulsion as ε 0 increases, might be supplemented by an additional pairing mechanism to account for superconductivity or at least for a quantitative understanding of the magnitude of T c . A number of additional candidates have been proposed involving: (i) residual coupling to critical TO modes missing in the dynamical screening model 20,43,44 ; (ii) plasmons in the conduction electron system 21 , which must be included for minimal consistency of any proposed model; (iii) multi-valley transition processes 9,13 ; (iv) non-polar acoustic phonons (see, e.g., the Appendix in ref. 21 45 ; and other distinct models, e.g., refs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…repulsion as ε 0 increases, might be supplemented by an additional pairing mechanism to account for superconductivity or at least for a quantitative understanding of the magnitude of T c . A number of additional candidates have been proposed involving: (i) residual coupling to critical TO modes missing in the dynamical screening model 20,43,44 ; (ii) plasmons in the conduction electron system 21 , which must be included for minimal consistency of any proposed model; (iii) multi-valley transition processes 9,13 ; (iv) non-polar acoustic phonons (see, e.g., the Appendix in ref. 21 45 ; and other distinct models, e.g., refs.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the mediation of polar optical modes, while of key importance in reducing the Coulomb repulsion as ε 0 increases, might be supplemented by an additional pairing mechanism to account for superconductivity or at least for a quantitative understanding of the magnitude of T c . A number of additional candidates have been proposed involving: (i) residual coupling to critical TO modes missing in the dynamical screening model 20 , 43 , 44 ; (ii) plasmons in the conduction electron system 21 , which must be included for minimal consistency of any proposed model; (iii) multi-valley transition processes 9 , 13 ; (iv) non-polar acoustic phonons (see, e.g., the Appendix in ref. 21 ; (v) non-polar soft optical phonons 12 ; (vi) currents associated with transverse polar optical modes; (vii) non-cancelling contributions of polar optical modes in between Ω( q ) and Ω LO 21 ; (viii) phonon modes localized around the dopant impurity sites 23 ; (ix) effects associated with Sr disordering at low temperatures 45 ; and other distinct models, e.g., refs.…”
Section: Resultsmentioning
confidence: 99%
“…One of the reasons is that the superconductivity starts to emerge at an extraordinarily low carrier density on the order of 10 17 cm −3 [64,65], where the conventional Migdal-Eliashberg theory is not applicable. Although various studies have proposed possible origins of the dilute superconductivity [66][67][68][69][70][71][72][73], there is no sufficient understanding of the pairing mechanism even now. Another reason is a quantum paraelectricity in SrTiO 3 , which prevents a long-range ferroelectric order by its quantum fluctuations [74,75].…”
Section: A Srtiomentioning
confidence: 99%
“…The recent debate about appropriate models [10][11][12][13][14][15][16][17][18][19][20][21]7] mostly swirls around the question of which phonons provide the superconducting pairing and how. Showing experimentally which phonons are the most relevant is not a trivial task either: Some recent experiments on approaching the quantum paraelectric to ferroelectric phase transition show correlations of the ferroelectric phase with superconductivity [22][23][24][25][26][27][28].…”
mentioning
confidence: 99%